2020
DOI: 10.30682/nm2003h2
|View full text |Cite
|
Sign up to set email alerts
|

Changing Route: Common Action on Food Systems Transformation in the Mediterranean

Abstract: The Coronavirus pandemic has revealed the fragility of our food systems, affecting all dimensions of food security and nutrition across the world. It has highlighted how deeply our world is interconnected and the importance of better recognising and understanding the interconnections that are intrinsic to these systems and their key role in pursuit of the SDGs of the 2030 Agenda. There is now, more than ever, a stronger need for a “route change” towards a common action on food systems transformation. Dialogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These processes allow a more comprehensive analysis of the needs and the eventual impact of the actions, ensure that all stakeholders are committed, accountable and contribute effectively to implementing the agreed actions for moving towards sustainable food systems and achieving results at scale. This is the objective, for example, of the SFS-MED platform, a multi-stakeholder initiative that FAO, CIHEAM and the Union for the Mediterranean Secretariat are developing in the Mediterranean as part of the One Planet Network's Sustainable Food System Programme, and which is featured as a unique opportunity to pilot and validate a "change of route" in the region (Ridolfi et al, 2020) by providing a space for policy, science and technical dialogue in shaping pathways towards more sustainable food systems by 2030.…”
Section: Multi-stakeholder Collaborationmentioning
confidence: 99%
“…These processes allow a more comprehensive analysis of the needs and the eventual impact of the actions, ensure that all stakeholders are committed, accountable and contribute effectively to implementing the agreed actions for moving towards sustainable food systems and achieving results at scale. This is the objective, for example, of the SFS-MED platform, a multi-stakeholder initiative that FAO, CIHEAM and the Union for the Mediterranean Secretariat are developing in the Mediterranean as part of the One Planet Network's Sustainable Food System Programme, and which is featured as a unique opportunity to pilot and validate a "change of route" in the region (Ridolfi et al, 2020) by providing a space for policy, science and technical dialogue in shaping pathways towards more sustainable food systems by 2030.…”
Section: Multi-stakeholder Collaborationmentioning
confidence: 99%
“…It is interesting to orient the research towards the quality analysis of the foodstuffs groups (nutritional quality). For this purpose, national surveys should be conducted in order to determine the adherence of the population to the Mediterranean diet allowing the measurement of indexes and scores (Ridolfi et al, 2020;Lacirignola et al, 2015;Souissi et al, 2019;FAO, 2016;Visinoni et al, 2017).…”
Section: Conclusion and Policy Measuresmentioning
confidence: 99%
“…Several scientific works confirmed that the Mediterranean diet, formerly adopted in the Mediterranean countries, is considered as a nutritional and healthy food model with important benefits for the population (Ridolfi et al, 2020;Dogui et al, 2021;Med diet project, 2017). Declared an "intangible heritage of humanity" in 2010, the Mediterranean model is not a homogeneous model in the Mediterranean area due to regional social, cultural and economic variations (UNESCO, 2010; Khaldi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reflected on sustainability or positive externalities (Berbel 2020; Melgarejo 2019; Skevas 2020); or the innovations carried out (Boazar, Abdeshahi, and Yazdanpanah 2020; Camacho 2002; Gómez 2007; Gómez and Gil 2014; Maroto and Baixauli 2016). Even more, the COVID-19 pandemic has triggered to pursue a more sustainable approach concerning healthy and sustainable food consumption (Ridolfi et al, 2020), but that also entails a wiser consumption of water and strategies in order to reduce it.…”
Section: Introductionmentioning
confidence: 99%